The non‐professionally affiliated (NPA) worker as co‐producer of public services: how is the role experienced in UK mental health services?. Issue 3 (7th June 2018) - Procter, Stephen; Harrison, Deborah; Pearson, Pauline; Dickinson, Claire
Abstract: Recent workforce reforms have led to the widespread expansion of non‐professionally affiliated (NPA) support and assistant roles within UK public services. Research into these roles has been confined to a limited range of settings, with a focus on the consequence of change for professional workers. This article explores the emergence of 'co‐production', whereby NPA workers contribute alongside the professional in a distinct, complementary way. Findings are drawn from semi‐structured interviews with frontline workers and managers within the context of mental health workforce reform. The results build a picture of NPA working life characterised in part by autonomy and responsibility. At the same time, NPA workers rely on colleagues for support and are subject to being used indirectly by professionals. Contextual influences are considered. The conceptual implications of the analysis are brought out, both for the NPA role itself and for the broader issues involved in front line service work.